Steganography using Optimal Least Significant Bit with greedy algorithm - Tan, Edrian Jay Z.; Ultra, John D. (2016)
In steganography, the robustness of the stego object is an important criterion in evaluating a technique. Maintaining this property gets harder as the size of the secret message increases, making the stego object less robust and susceptible to attacks from third parties. Numerous ways to increase the imperceptibility and security of the stego object have been studied. In this paper, the Optimal Least Significant Bit (OLSB) technique was used to embed secret messages into a digital image. A greedy algorithm was used to find the optimal substitution vector for a specific embedding of a secret message to a cover image. The greedy algorithm was compared to an implementation of an improved Bat algorithm and showed satisfactory results based on the quality of the output substitution vectors and its average running time.
Undergraduate thesis (B.S. Computer Science) -- University of the Philippines, Tacloban.
Keywords: Steganography; Optimal Least Significant Bit (OLSB).; Greedy algorithm